2011
DOI: 10.1242/dev.074153
|View full text |Cite
|
Sign up to set email alerts
|

Pitx1 is necessary for normal initiation of hindlimb outgrowth through regulation of Tbx4 expression and shapes hindlimb morphologies via targeted growth control

Abstract: SUMMARYThe forelimbs and hindlimbs of vertebrates are morphologically distinct. Pitx1, expressed in the hindlimb bud mesenchyme, is required for the formation of hindlimb characteristics and produces hindlimb-like morphologies when misexpressed in forelimbs. Pitx1 is also necessary for normal expression of Tbx4, a transcription factor required for normal hindlimb development. Despite the importance of this protein in these processes, little is known about its mechanism of action. Using a transgenic gene replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 35 publications
6
60
0
Order By: Relevance
“…This result is in an agreement with another study carried out on rabbit embryos (Rivas and Shapiro, 2002). bud formation is Pitx1 and Tbx4, that expressed by limb mesenchymal cell (Duboc and Logan, 2011). Mesenchyme cells of the limb bud converted into chondrogenic cells resulted in the formation of cartilage primordia by day 14 of gestation which developed into cartilage template by day 15, when chondrogenic cells secreted glycosaminoglycan (GAG) rich cartilage matrix as confirmed by Safranin-O positive staining.…”
Section: Development Of Humerus From New Zealand White Rabbitssupporting
confidence: 92%
“…This result is in an agreement with another study carried out on rabbit embryos (Rivas and Shapiro, 2002). bud formation is Pitx1 and Tbx4, that expressed by limb mesenchymal cell (Duboc and Logan, 2011). Mesenchyme cells of the limb bud converted into chondrogenic cells resulted in the formation of cartilage primordia by day 14 of gestation which developed into cartilage template by day 15, when chondrogenic cells secreted glycosaminoglycan (GAG) rich cartilage matrix as confirmed by Safranin-O positive staining.…”
Section: Development Of Humerus From New Zealand White Rabbitssupporting
confidence: 92%
“…Individuals with Liebenberg syndrome have long arms, elongated metacarpals and dramatically affected elbow joints that have features similar to a knee joint, including a patella [29]. In the mouse, the relatively longer hindlimb metatarsals compared to forelimb metacarpals are generated by increasing the growth rates of the metatarsal primordia during a discrete time-window [30]. This accelerated growth of the metatarsals is regulated by Pitx1 and the growth rate of metacarpal elements can be made metatarsal-like by ectopic expression of Pitx1 in the forelimb [30].…”
Section: Tbx5 and Tbx4 Serve As Markers Of The Subdomains Within The Lpmmentioning
confidence: 99%
“…4.1(C)). Similarly, in a pitx1 −/− mutant hindlimb, the resulting partial loss of tbx4 expression results in defective limb outgrowth and this can be rescued by ectopic hindlimb expression of tbx5 (Duboc and Logan, 2011a). Thus the significance of the limb bud-specific expression of tbx4 and tbx5 is only that their different cis-regulatory apparatus ensures the expression in both pairs of limb (LPM, pink).…”
Section: Initial Functions Of Tbx4 and Tbx5mentioning
confidence: 99%
“…For example pitx1, involved as we have seen in the earliest aspects of hindlimb bud specification, continues to operate in hindlimb development throughout. This gene is required for subtle patterning of soft tissues, particularly for the presence of specific small muscles and tendons (Duboc and Logan, 2011a), and it also controls metatarsal morphogenesis by modulating growth rate in the different digits. A global study in which all mouse enhancers known to drive expression in limb buds were assessed for Pitx1 binding in ChIP seq experiments demonstrated that >67% of these enhancer sequences include a Pitx1 peak (Infante et al, 2013).…”
Section: From Regulatory State Patterns To Morphogenesismentioning
confidence: 99%